Victimization and Post-traumatic Stress Disorder of Victims of Terrorism in Indonesia (Medico Legal Update, 2021)
Terror attacks result in prolonged traumatic effects on both victims and survivors. Previous studies haveanalyzed the effects of terror attacks on the psychological condition of post-traumatic stress disorder fromexposure to terrorist attacks. This article discusses victims of terrorism in Indonesia based on data from2008-2018. The use of data over the span of several years is important to determine the trend of victimizationso that a response can be made to reduce the suffering of victims. This perspective also includes counterterrorism efforts to minimize the suffering of victims directly or indirectly due to terrorism. The criminaljustice system can also reform paradigmatically, providing fulfillment of the rights of victims in accordancewith applicable legal norms.